(untitled) (Research, Society and Development, 2021)
This work presents a study of cold-formed steel (CFS) profiles not standardized by standard, lipped channel section with top flange inclined at 30°. The goal is to determine an equation for the local buckling coefficient (kl) to apply the Effective Section Method (ESM) proposed by the Brazilian standard. Profiles are analyzed for axial compressive stress and simple bending moment. Analyzes were performed using GBTUL software. For the parametric study, 95 profiles with different geometric variations were developed. From the signature curves of each analysis, the respective critical axial compressive load values for local buckling and critical bending moment associated with local buckling are obtained. Using the Brazilian normative prescriptions and the results obtained, it was possible to determine the value of kl for each of the analyzed profiles. Thus, according to the Effective Section Method presented by the standard, two equations were proposed to determine the local buckling coefficient (kl), one for centered compression and one for bending moment around the axis of greatest inertia. The equations proved to be adequate to be used in the Effective Section Method for the type of profile presented, lipped channel section with flange inclined at 30°.